COMPLEX MITOCHONDRIAL DNA IN LEUKEMIC AND NORMAL HUMAN MYELOID CELLS - Clayton, David A. (1969)
Mitochondrial DNA's from the peripheral blood of 14 patients with granulocytic leukemia contained a circular dimer form. No such structure could be found in M DNA's from three patients with nonmalignant proliferations of granulocytes. The frequency of the circular dimer form is reduced upon treatment with antileukemic drugs. The above results suggest that a significant relation exists between the formation and presence of the circular dimer M DNA form and granulocytic leukemia in man.